PRODUKTIVITAS RUMPUT Panicum maximum cv. Trichoglume YANG DIPUPUK DENGAN JENIS DAN DOSIS PUPUK ORGANIK BERBEDA - N. M., WITARIADI; KUSUMAWATI, N. N. (Majalah Ilmiah Peternakan, 2022)
This study aims to determine the productivity of Panicum maximum cv. Trichoglume with different types and dosage of organic fertilizer. The trial was for 2 months, with factorial completely randomized design (CRD). The first factor were type of organic fertilizer: S (cow manure); K (goat manure); and SK (cow and goat manure), and second factor was dosage of organic fertilizer: D0 (0 ton ha-1); D1 (10 tons ha-1); D2 (20 tons ha-1); and D3 (30 tons ha-1). There were 12 treatment combinations and each treatment was repeated 4 times. The observed variables : growth variables, yield variables and growth characteristics variables. The results showed that there was no inter- action between the type and dosage of organic fertilizer in increasing the productivity of Panicum maximum cv. Trichoglume. The use of cow and goat manure (SK) can increase the number of leaves, number of branches, plant height, leaf dry weight, stem dry weight, total dry weight of forage, leaf area per pot, ratio of leaf dry weight to stem and weight ratio completely dry forage with roots. Dosage of organic fertilizer from 10-30 tons ha-1 can increase the productivity of Panicum maximum cv. Trichoglume on the variable number of tillers, number of leaves, number of branches, dry weight of leaves, dry weight of stems, total dry weight of forage, leaf area per pot, ratio of dry weight of leaves to stem and ratio of total dry weight of forage to roots, and the best results in dosage of 30 tons ha-1. It was concluded to increase the productivity of Panicum maximum cv. Trichoglume with cow and goat manure fertiliza- tion at dosage 30 tons ha-1.